Chromatin Conformation in Development and Disease - Boltsis, Ilias; Grosveld, Frank; Giraud, Guillaume; Kolovos, Petros (Frontiers in Cell and Developmental Biology, 2021)
Chromatin domains and loops are important elements of chromatin structure and dynamics, but much remains to be learned about their exact biological role and nature. Topological associated domains and functional loops are key to gene expression and hold the answer to many questions regarding developmental decisions and diseases. Here, we discuss new findings, which have linked chromatin conformation with development, differentiation and diseases and hypothesized on various models while integrating all recent findings on how chromatin architecture affects gene expression during development, evolution and disease.